Factor Va alternative conformation reconstruction using atomic force microscopy - Chaves, Rui C.; Dahmane, Selma; Odorico, Michael; Nicolaes, Gerry A.F.; Pellequer, Jean-Luc (Thrombosis and Haemostasis, 2014)
Protein conformational variability (or dynamics) for large macromolecules and its implication for their biological function attracts more and more attention. Collective motions of domains increase the ability of a protein to bind to partner molecules. Using atomic force microscopy (AFM) topographic images, it is possible to take snapshots of large multi-component macromolecules at the single molecule level and to reconstruct complete molecular conformations. Here, we report the application of a reconstruction protocol, named AFM-assembly, to characterise the conformational variability of the two C domains of human coagulation factor Va (FVa). Using AFM topographic surfaces obtained in liquid environment, it is shown that the angle between C1 and C2 domains of FVa can vary between 40° and 166°. Such dynamical variation in C1 and C2 domain arrangement may have important implications regarding the binding of FVa to phospholipid membranes.
Keywords: Coagulation factors; imaging; phospholipids; protein structure / folding; atomic force microscopy